(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Like any other quality (virtue), creativity is not formed suddenly. Creativity is consistently formed and developed at certain stages. Possessing creative qualities of a teacher directs his personal abilities, natural and social energy to quality and efficient organization of professional activities.